“Efecto cicatrizante del croton lechleri“sangre de drago”en cirugía de terceros molares en el Hospital Provincial General Docente Riobamba” - Pérez Aguiar, Lisette Adriana (2017)
The research titled Collagen (dragon's blood) healing effect in third molar surgery aims to check the healing effect of the same drug as an alternative to ensure scarring without risk of infection after third molar surgery. The present investigation was carried out in the Provincial General Hospital of Riobamba, a field study was carried out applying 3 drops of blood of drago directly in the alveolus after performing the third moral surgery observing the instantaneous formation of the sanguineous clot, In addition, samples of patients were obtained with the application and without the application of Dragon blood for a culture, as a result in the samples: without Croton lechleri (blood of dragon) presence of bacteria while in the samples with Croton lechleri ) There is no bacterial presence and a longitudinal design that seeks to relate the variables through the collection of data in a given time to refer to determinants and consequences. The results obtained seek to find a new medicinal alternative to decrease bacterial proliferation and ensure healing of tissues. Dental extraction is the most frequently performed surgical procedure within oral surgery. In dental practice the main thing is to avoid infection to promote tissue healing, a physiological process of great importance, not finding wound infection is one of the basic pillars to ensure the success of any type of treatment in the area of surgery oral.